Faktor-Faktor Yang Melatarbelakangi Pembentukan Identitas Diri Pad a Remaja Transgender Di Perkumpulan Yotha Naungan PKBI DIY - Maria Nataliani Novatsiana Lagut, Sri Hendarsih, Christin Wiyani (Medika Respati : Jurnal Ilmiah Kesehatan, 2016)
Background : of identity may be influenced several idol, and experience ofsocial Lack ofsupport from these factors cause deviation in the formation self identity as experienced by transgender teens. Objective' To identify the factors which influence the formation of self identity on transgender teens. Research method . This research was conducted at Yotha association under the of PKBI Yogyakarta. It qualitative phenomenological design by interviewing 3 infromants. Result· The discort between transgender teen and his father as well as the absence of atherbecause he did not assume his responsibility rearing after divorce has made his oedipus "rln,.,rlJ"V failed to his father as the male The which was conducted his mother resulted in a strong bond with his mother and made her as an idol and model in his identification process of being woman. The failure of oedipus complex and bond to his mother while the latent made them afraid of and doubt about his and more comfortable to join female peers. Motivated and treated as woman while love by male peer; he was stimulated to respond and playa role as a woman, Conclusion. The role of family as a model of influence ofidol and socializing with peers who provide social role for significantly influence the formation of self identity.Keywords. self identity